2017
DOI: 10.1073/pnas.1707357114
|View full text |Cite
|
Sign up to set email alerts
|

Critical structural fluctuations of proteins upon thermal unfolding challenge the Lindemann criterion

Abstract: Internal subnanosecond timescale motions are key for the function of proteins, and are coupled to the surrounding solvent environment. These fast fluctuations guide protein conformational changes, yet their role for protein stability, and for unfolding, remains elusive. Here, in analogy with the Lindemann criterion for the melting of solids, we demonstrate a common scaling of structural fluctuations of lysozyme protein embedded in different environments as the thermal unfolding transition is approached. By com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 55 publications
8
49
0
Order By: Relevance
“…Another important aspect is that conformations at different temperatures can be generated, from the ambient regime to well above melting. A systematic difference between experimental and computed absolute T m values was observed, as already reported for other systems . This is likely due to a combination of force‐field limitations, finite sampling, and to the temperature reconstruction method.…”
Section: Resultssupporting
confidence: 66%
“…Another important aspect is that conformations at different temperatures can be generated, from the ambient regime to well above melting. A systematic difference between experimental and computed absolute T m values was observed, as already reported for other systems . This is likely due to a combination of force‐field limitations, finite sampling, and to the temperature reconstruction method.…”
Section: Resultssupporting
confidence: 66%
“…By means of neutron scattering experiments and numerical simulations, it was found that the low-temperature evolution of the mean square displacement (MSD) of the polymer atoms shows a slope change at a temperature T C 250 K, due to the onset of anharmonic motions [23]. This phenomenon in microgels is similar to the known dynamical transition observed in proteins [24,25] and appears to be strongly driven by PNIPAM-water interactions [26].…”
Section: Introductionmentioning
confidence: 91%
“…In order to answer that question, we consider using the Lindemann criterion developed originally for the melting of a solid crystal [ 52 ]. The Lindemann value has been adapted to the case of proteins by replacing the crystal lattice constant, , with an average nonbonded distance [ 53 , 54 ]. Katava et al provided experimental estimates of the from inelastic neutron scattering for hen egg white lysozyme (HEWL) and, assuming = 4.75 Å, found a Lindemann value at the protein melting temperature ( ) of ~0.17–0.18, driven by the mixing in of a greater proportion of unfolded state fluctuations [ 54 ].…”
Section: Resultsmentioning
confidence: 99%